Local subsidence flow in a surface boundary layer on the sloped ice sheet at Mizuho Station, East Antarctica (extended abstract) - Kobayashi, Shun'ichi; Ishikawa, Nobuyoshi; Ohata, Tetsuo; Kawaguchi, Sadao (1982)
P(論文) departmental bulletin paper